Public-Private Partnership in BRICS Countries: Experience and Prospects of Implementation - T. S. Cheremnaya (Vestnik MGIMO-Universiteta)
Abstract: In the article the questions of application of public-private partnership (PPP) for the implementation of projects in infrastructure in the BRICS countries (BRICS). The analysis is carried out on the basis of a comparison of the legal framework in the field of public-private partnership and concession legislation, as well as the experience gained in the implementation of projects. Using data from open sources, materials of the meetings of the authorities and business on the issues of implementation of publicprivate partnerships, statements of responsible persons developed a comparative table that identified and summarized trends in the development of public-private partnership in the BRICS countries. Examines global trends in the sphere of use of PPP mechanisms in the five countries, as well as key sectors in which PPP projects. Identified current problems in the implementation of projects in the preparatory phase and in case of change of technical and financial parameters of the project. The practical significance of the results of this study is the feasibility of extending public-private partnership in the implementation of joint projects in the BRICS countries. The results of the study can be used in the formation of the General strategy of development of infrastructure of BRICS countries on how in-country and inter-state levels.